First things first every day : because where you're headed is more important than how fast you're going - Covey, Stephen R.; Merrill, A. Roger; Merrill, Rebecca R. (New York : Simon & Schuster, 1997)
Contains a collection of daily thoughts based on the author's "First Things First," which describes a principle-centered approach to time management called the Quadrant II organizing process, designed to help people close the gap between what they feel is important and the way they really spend their time.
"A Fireside book.".
Companion volume to: First things first.
Adult
Keywords: Conduct of life; Time management; Conduct of life; Time management